Emotional Affinity of Children Toward Nature - Jabbar Ali, Anwer; Torkos, Henrietta (Technium Social Sciences Journal, 2023)
The aim of the current study is to investigate the role of emotional closeness towards nature in a sample of children from Iraq aged (4-9) years, passion towards nature develops through experiences with nature during childhood and that contact with nature, which can vary from green spaces in cities to landscapes have a really positive impact on many aspects of children’s lives from social interaction with each other to cooperation and play freely. The theoretical part, describes the basics in which children’s affinity towards nature is developed by national curriculum, both in Iraq and Romania. The results showed that in nature, children become expressive and eager to play with each other freely and break free of parental restrictions. Our results support the idea that closeness and experiences in nature are one possible way to stimulate pro-environmental intentions in children. This extends to previous studies showing that growing up near nature and spending time in nature are predictors of pro-environmental attitudes and behaviors.